Celebration and ceremony through life - Strader, Molly (East Carolina University, 2010)
This written report supports a creative thesis investigation about objects used for celebrations and ceremonies. My work in precious metals and textiles symbolically represents significant transitions in a human life. Individually, each object represents a meditation on the different aspects of life's transitions, depicting contemporary culture and the rites, rituals, and markers of time that bring people together through a lifetime. It is my personal interpretation of the natural world and religious ideologies that have inspired me to create works that express my connection to those events.
Keywords: Fine arts; Silk weaving; Art metal-work